A Study on Adoption of Improved Farm Practices by Hill Farmers of Almora District in Uttrakhand (Indian Journal of Extension Education, 2014)
Adoption of improved farm practices is being encouraged amongst hill farmers for their socio-economic development. The present study was conducted in Almora, Uttarakhand by taking a random sample of 60 farmers. The objectives were to know the extent of adoption of improved farm practices; relationship of the factors with adoption; and the constraints of adoption. Data were collected during 2011-12 by personal interview through pre-tested structured schedule. Findings showed that majority of the farmers belonged to medium adopter’s category (55.95%). The highest adoption was found in improved varieties of vegetables (71.67%) and least adoption was reported in mushroom production technology (1.67%). Risk bearing ability, change-proneness, level of aspiration, annual income and economic motivation were found to be most significantly correlated factors of adoption. The most serious constraint was identified as weather vagaries (83.33%). The findings of the study can help selecting suitable innovations to diffuse amongst hill farmers of this area.